Perancangan Sistem Informasi Data Jinayat Berbasis Web pada Kantor Dinas Syariat Islam Aceh - Putri Maulidia; Muhammad Wali; Harry Idwan (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2023)
The issue of managing Jinayat data at the Aceh Islamic Shariah Service Office can burden responsible employees. However, we have found an innovative solution to solve this problem. The author designed his web-based information system for Jinayat data, which allows him to manage Jinayat data more efficiently. In this article, the authors describe the research methods used, namely field research and literature research, and how extreme programming was developed. It also describes how to design this information system using the web programming language. This web-based information system facilitates access to Jinayat data and improves management. In addition, the author also describes the positive benefits and effects that the Aceh Islamic Shariah Service Office feels after using this information system. This information system will enable staff to manage his Jinayat data more efficiently and effectively, thereby benefiting the institution and society as a whole. By using the latest technology, the Aceh Shariat Islamic Office can manage the Jinayat data more efficiently. This article describes an innovative solution that can be applied to various government and private organizations that require information systems to optimize data management.